Metal-free synthesis of 3,3′-bisindolylmethanes in water using Ph₃C⁺[B(C₆F₅)₄]⁻as the pre-catalyst - Zhang, Zhenguo (2023)
Here, we report a highly efficient catalytic species generated from Ph3C+[B(C6F5)4]− by the water mediated Friedel-Crafts type reaction of indoles with carbonyl compounds to afford 3,3′-bisindolylmethanes (BIMs). This scalable method is applicable to a wide variety of carbonyl compounds, including unprotected sugar molecules and carbonyl compounds derived from drugs and natural products.